2022
DOI: 10.1123/jsr.2021-0197
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Virtual Reality Nonphysical Mental Training on Balance Skills and Functional Near-Infrared Spectroscopy Activity in Healthy Adults

Abstract: Context: Athletic skills such as balance are considered physical skills. However, these skills may not just improve by physical training, but also by mental training. The purpose of this study was to investigate the effects of mental training programs on balance skills and hemodynamic responses of the prefrontal cortex. Design: Randomized controlled trial. Methods: Fifty-seven healthy adults (28 females, 29 males), aged between 18–25 years, participated in this study. Participants were randomly assigned to 3 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Motor imagery and action observation are two clear examples of training opportunities that are more powerful when boosted by immersive virtual reality, both for motor recovery after stroke, [ 33 ] and improving the motor control of a body powered prosthesis [ 34 ]. Moreover, coordination and skill transfer (two important components in sports and in neuromotor rehabilitation) can also be better trained through mental training performed with immersive virtual reality [ 35 , 36 ]…”
Section: The Basis For Applying Metaverse-related Technology In Neuro...mentioning
confidence: 99%
“…Motor imagery and action observation are two clear examples of training opportunities that are more powerful when boosted by immersive virtual reality, both for motor recovery after stroke, [ 33 ] and improving the motor control of a body powered prosthesis [ 34 ]. Moreover, coordination and skill transfer (two important components in sports and in neuromotor rehabilitation) can also be better trained through mental training performed with immersive virtual reality [ 35 , 36 ]…”
Section: The Basis For Applying Metaverse-related Technology In Neuro...mentioning
confidence: 99%
“…More research and evidence from applied practice, however, is required to further clarify the advantages of using VR; and whether the virtual environment is evoking experiences and psychological states that are the same as, or at least similar to, the real world. Furthermore, evidence of the neuroscientific basis of potential VR training benefits (i.e., in terms of neural plasticity) is largely missing (with notable recent exceptions, e.g., Köyağasıoğlu et al, 2022) .…”
Section: Skill Acquisition Motor Learning and Control In Sportsmentioning
confidence: 99%
“…Due to its 360-degree nature and responsiveness to head movements, VR is more immersive than videos watched on screens (Pagé et al, 2019), which is currently the most common way to assist athletes in imagery interventions (Bedir & Erhan, 2021). Assuming an enhanced sense of presence is beneficial to imagery (Bedir & Erhan, 2021;Köyağasıoğlu et al, 2022), athletes should be able to image more effectively using VR.…”
Section: Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…In a virtual exercise experiment comparing the training benefits of virtual exercise from different perspectives, this study found that the more immersive first-view training significantly enhanced trainers' motivation and riding speed [ 11 ]. The experiment used virtual opponents for virtual obstacle running training, and virtual training was found to improve trainers' decision-making ability and enhance athletic performance by rating speed, stride count, and decision-making ability [ 12 ].…”
Section: Related Workmentioning
confidence: 99%